Psychometric properties of the God Locus of Health Control scale in a sample of mexicans with type 2 diabetes mellitus - Argüelles Nava, Vianey Guadalupe (2017)
The validity and reliability of the God Locus of Health Control (GLHC) scale were determined in a sample of 539 Mexican adults with type 2 diabetes mellitus. The validity analysis was based on the analysis of the GLHC scale’s items content and internal structure. The first procedure was conducted by six experts who evaluated the pertinence of the items adaptation. The second procedure consisted of a multiple-group confirmatory factor analysis by gender and age, aimed to evaluate the GLHC scale’s measurement invariance. Finally, reliability was estimated by means of coefficients ω and H. The confirmatory factor analysis demonstrated a six-item unifactorial structure, interpretable for the study population with measurement invariance by gender. Nevertheless, precautions should be taken when interpreting age-group comparisons. The magnitude of the construct reliability was high (>0.90). The results indicate that the GLHC scale may provide valid and reliable information to assess the God Locus of Health Control in Mexicans with type 2 diabetes mellitus.